2016
DOI: 10.3389/fphar.2015.00323
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hypertensive Herbs and their Mechanisms of Action: Part I

Abstract: The use of herbal therapies for treatment and management of cardiovascular diseases (CVDs) is increasing. Plants contain a bounty of phytochemicals that have proven to be protective by reducing the risk of various ailments and diseases. Indeed, accumulating literature provides the scientific evidence and hence reason d'etre for the application of herbal therapy in relation to CVDs. Slowly, but absolutely, herbal remedies are being entrenched into evidence-based medical practice. This is partly due to the suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 225 publications
(438 reference statements)
1
106
0
3
Order By: Relevance
“…It induces endothelial-cell dysfunction, oxidative stress, and inflammation 52,53) through the release of proinflammatory cytokines, such as TNF-α and IL-6. 53,54) IL-1 is one of the most critical molecules involved in neuroendocrine and neurobehavioral stress responses. Many types of stressors induce the production of IL-1, both in the periphery and within the brain.…”
Section: Discussionmentioning
confidence: 99%
“…It induces endothelial-cell dysfunction, oxidative stress, and inflammation 52,53) through the release of proinflammatory cytokines, such as TNF-α and IL-6. 53,54) IL-1 is one of the most critical molecules involved in neuroendocrine and neurobehavioral stress responses. Many types of stressors induce the production of IL-1, both in the periphery and within the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Sal A, Sal B, Danshensu, and tanshinones are its most effective ingredients. A combination treatment of Danshen and Gegen was shown to lower BP in SHRs and to induce relaxation of several kinds of arteries including porcine coronary arteries, rat aorta, and basilar arteries (Al Disi et al, 2015). Apart from its vasodilatory capacity, Danshen expresses additional anti-hypertensive parameters such as antioxidative, anti-proliferative, and anti-inflammatory activities which will be discussed in more details in Section “Mechanisms of Plant Products in the Attenuation of CVDs.”…”
Section: Application Of Chm In Cvdsmentioning
confidence: 99%
“…8,9 It has been extensively reported that in endothelium-intact rings, Ach-induced relaxation is completely reversed by NG-nitro-Larginine-methylester (L-NAME); a selective inhibitor of nitric oxide synthase. 1 In vascular tone regulation, both endothelium-derived relaxing factors (EDRFs) and endothelium-derived contracting factors (EDCFs) produce their effect via interaction between the endothelium and vascular smooth muscle cells. Endothelial factors that are most commonly held to account for the actions of vasodilator drugs, which may also explain the actions of vasodilator medicinal plants ( Vasorelaxants which act through interference with Ca 2+ influx via VOCC or ROCC are usually differentiated using relaxation responses of isolated arterial rings precontracted with high K + (VOCC) or phenylephrine (ROCC).…”
Section: Vascular Endotheliummentioning
confidence: 99%